Stability of the primary organization of nucleosome core particles upon some conformational transitions. - Zayetz, V W (1981)
The sequential arrangement of histones along DNA in nucleosome core particles was determined between 0.5 and 600 mM salt and from 0 to 8 M urea. These concentrations of salt and urea up to 6 M had no significant effect on the linear order of histones along DNA but 8 M urea caused the rearrangement of histones. Conformational changes in cores have been identified within these ranges of conditions by several laboratories 8-21. Also, abrupt structural changes in the cores, apparently their unfolding, were found by gel electrophoresis to occur at urea concentration, between 4 and 5 M. 600 mM salt and 6 M urea were shown to relax the binding of histones to DNA in cores but do not however release histones or some part of their molecules from DNA. It appears therefore that nucleosomal cores can undergo some conformational transitions and unfolding whereas their primary organization remains essentially unaffected. These results are consistent with a model of the core particles in which the histone octamer forms something like a helical "rim" along the superhelical DNA and histone-histone interactions beyond the "rim" are rather weak in comparison with those within the "rim".